(untitled) (Research, Society and Development, 2023)
Medicinal plants and phytotherapy are therapies commonly used to promote well-being in health. Among the populations that use this health practice, low-income residents of suburban areas stand out, as it is a strategy that involves not only scientific foundations, but also other determinants such as interpersonal relationships, culture, environment, beliefs and socioeconomic context. Considering the Covid-19 pandemic scenario, which is strongly characterized by the constant updating of knowledge, popular medicine has become a scientifically supported and valid alternative in the process of mitigating and/or curing the symptoms of SARS-CoV-2 infection. Therefore, the present study aims to demonstrate the relationship between the sociodemographic profile of the suburban population and the therapeutic use of medicinal plants and herbal medicines in the symptomatological treatment of Covid-19, through exploratory descriptive research, with a qualitative approach, through the application of a semi-structured interview. The present study identified the following profile of consumers of medicinal plants: 100% women, with an average age of 48 years, 50% with complete primary education and residing in the semi-peripheral region; highlighting the relationship between this population profile and therapeutic practice aimed at Covid-19.